Sectioning and Counting of Motor Neurons in the L3 to L6 Region of the Adult Mouse Spinal Cord. Issue 5 (26th May 2022) - Austin, Adele; Beresford, Lynn; Price, Georgia; Cunningham, Tom; Kalmar, Bernadett; Yon, Marianne
Abstract: Histology is the study of the microscopic structure of tissues. This protocol permits the generation of frozen transverse sections of lumbar spinal cord regions L3 to L6. It enables counting of murine ventral horn lumbar motor neurons in a reproducible manner. Methods include spinal column dissection, hydraulic extrusion, and histological processing. The preparation for cryo‐sectioning includes embedding lumbar spinal cord in optimal cutting temperature (OCT) medium. The correct orientation of the tissue is critical as calculating the amount of tissue to discard saved time overall. Specific details regarding section thickness and mounting are described. These requirements not only allow optimum coverage of specific regions but also ensure that no individual motor neuron was counted twice. The Nissl bodies of the motor neurons were stained using gallocyanin. The sections obtained are all of a comparable area and quality assurance is consistent. The specificity of the staining enables the scientist to identify and reliably quantify lumbar motor neurons. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Euthanasia of mouse and isolation of spinal cord Basic Protocol 2 : Hydraulic extrusion of the spinal cord Basic Protocol 3 : Identification of the lumbar region Basic Protocol 4 : Embedding cord in OCT Basic Protocol 5 : Collection of frozen sections onto slides Basic Protocol 6 : Gallocyanin staining Basic Protocol 7 : Motor neuron counting